Burden of Care and Quality of Life in Home Caregivers of Patients With Stroke in Iran. Issue 4 (November 2019) - Masoudian, Nooshin; Sarmadi, Mohammad; Najafi, Rasool; Najafi, Fereshteh; Maleki, Shirin
The purpose of this study was to investigate the relationship between Burden of Care and Quality of Life in informal home caregivers of stroke patients in Iran. Also we were trying to explore the factors that affect the burden of care. In this cross-sectional study, we have selected 62 informal home caregivers of the patients admitted to "the stroke outpatient unit of the neurology clinic" of the central hospital in Semnan province, Iran, to take part in the investigation. We interviewed them using the Caregiver Burden Inventory and SF-36 Questionnaire for assessing their quality of life. There was a negative and significant correlation between different aspects of quality of life and burden of care. In the bivariate regression model, being married and having lower levels of education (minimum years of schooling) were associated with higher levels of the burden. Our study shows that increasing burden of care in informal home caregivers reduces the quality of life in all domains. Thus, the results of this study indicate that an increase in the burden of caregiving on caregivers lowers their quality of life in all aspects; especially, caregivers who provide care to their spouses encountered more burden. Therefore, these caregivers must be in the center of interest while planning to reduce the burden of care.